Assessment of clinical and radiographic efficiency of manual and pediatric rotary file systems in primary root canal preparation: a randomized controlled clinical trial - Shimaa M. Hadwa; Rehab F. Ghouraba; Ibrahim A. Kabbash; Shaimaa S. EL-Desouky (BMC, 2023)
Abstract Introduction The success of primary teeth pulpectomy is strongly reliant on instrumentation techniques and their impact on obturation quality & postoperative pain. Recently, pediatric rotary file systems have been implemented. Aim to compare two pediatric rotary file systems (Kedo-S-Square & Fanta AF™ Baby) with manual K-files concerning obturation quality, instrumentation time, and postoperative pain in root canal preparation of primary molars using cone beam computed tomography (CBCT). Methods A randomized clinical trial was conducted with the trial registration number (TRN: NCT05619796 and date of registration: (17/11/2022) on sixty primary lower 2nd molars in healthy children aged 4-7 years. Molars were assigned randomly to three groups (n = 20). Group-I and -II were prepared with Kedo-S-Square & Fanta AF™Baby rotary systems respectively while group-III was prepared with a manual K-file. Instrumentation time was recorded using a stopwatch. CBCT was used to assess obturation quality immediately & recorded as optimal, underfilled, or overfilled. Postoperative pain was evaluated at 6, 12, 24, 48 h-time intervals using a four-point pain intensity scale. Statistical analysis was performed for the collected data. Results Among the three groups, group-I revealed a greater number of optimally filled teeth (85%) & less instrumentation time (74.75 s) followed by group-II & manual-K file group (p < 0.05). The hand K-file group had significantly more postoperative pain than the two rotary groups (p < 0.05). Conclusion the tested rotary file systems resulted in better obturation quality, less instrumentation time, and less postoperative pain compared to manual-K files during primary teeth pulpectomy.